2021
DOI: 10.1089/gtmb.2020.0263
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the TaqI (rs731236 T>C) Gene Polymorphism and Dental Caries Risk: A Meta-analysis

Abstract: This study investigated the association of the TaqI (rs731236 T>C) polymorphism in the VDR gene with dental caries. Methods: A comprehensive literature search was performed in PubMed, Web of Science, Embase, SinoMed (the Chinese biomedical literature service system), and the Wiley Online Library. Overall comparisons and subgroup analyses based on ethnicity and the presence of dental caries in dentition were performed. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to assess associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
3
2
2
Order By: Relevance
“…In our study, the frequency of T (known as T because it is not cleaved by Taq I) and C (also known as t because it is cleaved) alleles of the CC, CT and TT genotypes did not show significant differences between groups, indicating that this polymorphism does not contribute to oral mucositis. In contrast to our data, the CC/CT genotype was associated with periodontitis (Hamrun et al, 2022) and the C allele and CC genotype were associated with caries risk in children (Lei et al, 2021).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, the frequency of T (known as T because it is not cleaved by Taq I) and C (also known as t because it is cleaved) alleles of the CC, CT and TT genotypes did not show significant differences between groups, indicating that this polymorphism does not contribute to oral mucositis. In contrast to our data, the CC/CT genotype was associated with periodontitis (Hamrun et al, 2022) and the C allele and CC genotype were associated with caries risk in children (Lei et al, 2021).…”
Section: Discussioncontrasting
confidence: 99%
“…The Bsm I (rs1544410), Fok I (rs2228570) and Taq I (rs731236) polymorphisms in the VDR gene are among the most studied and have been associated with oral diseases such as cancer, lichen planus, caries, periodontitis and temporomandibular disorders (Bektas‐Kayhan et al, 2010; Hamrun et al, 2022; Kujundzic et al, 2016; Lei et al, 2021; Yildiz et al, 2021). VDR methylation status was assessed in hand‐foot‐and‐mouth disease associated with enterovirus 71 in children (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We found that homozygous (TT or CC) genotype at the rs731236 locus was associated with a 1.33-fold higher risk of caries than the heterozygous (TC) genotype (OR = 1.33, 95% CI 1.06-1.67, P = 0.02), which differs from the ndings of Lei et al [40] In Lei's study, rs731236 polymorphism with dental caries in the allele contrast model (C vs. T) and in the recessive genetic model (CC vs. TT/CT). This may be because, in our study, the subjects included were all ≤ 18 years old, and the oral environment, dietary habits, and microbial ora of adolescents differ from those in middle-aged and older adults [41] , who were also included in the study by Lei et al Moreover, basal and induced VDR expression can be regulated by environmental, genetic, and epigenetic factors [42] , which may account for the observed differences in research results.…”
Section: Discussioncontrasting
confidence: 90%
“…An insertion/deletion polymorphism in the gene encoding angiotensin converting enzyme may be related to permanent tooth caries but not to primary tooth caries, especially in women in the Czech population [45] . This study found similar results, in that the homozygous (TT or CC) genotype of rs731236 was associated with a higher risk of dental caries in permanent teeth than the heterozygous (TC) genotype under the overdominant genetic model (OR = 1.48, 95% CI: 1.07-2.03, P = 0.02), similar to the ndings of Lei et al [40] , suggesting that genetic polymorphisms at the rs731236 locus are likely to affect the incidence of dental caries in permanent teeth but not in primary and mixed dentition.…”
Section: Discussionsupporting
confidence: 89%
“…According to the World Health Organization, dental caries (hereafter termed "caries") is the third-leading major disease that seriously impacts human health (after cancer and cardiovascular disease; Lei et al, 2021). Consistently, a significant amount of research has been conducted on its development and etiology.…”
Section: Introductionmentioning
confidence: 99%